APLIKASI MODEL MANN-KENDALL DAN SEN’S (MAKESENS) UNTUK MENDETEKSI PERUBAHAN IKLIM - Sutapa, I Wayan (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2014)
Various scientific studies illustrate that carbon dioxide (CO2) in the atmosphere layer that is a consequence of the result of the combustion of coal, timber, oil and gas, has increased by almost nearing 20 % since the start of the industrial revolution. Industrial area are built almost in the entire continent of the world has resulted in waste of “Greenhouse Gases (GHG) such as carbon dioxide (CO2), methane (CH4) and nitrousoksida (N2O) that caused the blanket effect. The purpose of this research was to detect the presence or absence of climate change and determine the projected climate change due to global warming. This research was conducted in the city of Palu, Central Sulawesi, using daily data and analyzed on a daily, monthly and yearly. Trend projections of climate change and changes in the method of analysis Makesens (Mann - Kendall and Sen 'S). The conclusion of this research is the change of climate in the city of Palu is characterized by slowly increasing temperature , increased precipitation and decreased evapotranspiration and the results of the calculation value of Z indicates Makesens method occurs climate trend, either positive direction (increasing) and negative (decreasing). Regression equation projected annual average temperature (as an example) is; f (year) = 0.018 (year - first year) + 26.931. Keywords: climate change, Makesens, Palu